Planeación urbana en México en período de crisis, 1983-1984 - Garza Villarreal, Gustavo (El Colegio de México A.C., 1986)
The aim of this article is to analyze the features of the major urban-regional programs carried out under the Administration of President Miguel de la Madrid Hurtado, who took office shortly after a grave economic crisis hit the country. Specifically, an appraisal is made of the nation-wide objectives of the National Development Plan for 1 983-1988, as well as two of the seven programs which address this issue either in part or in their entirety, i.e., the Program for the Development of the Metropolitan Area of Mexico City and the Central Region of Mexico and the National Program for Urban Development and Housing, 1984-1988. Both programs are reviewed within the context of theories of urban and regional planning. An attempt is made to determine the extent to which they fall within the period of institutionalized urban policies embarked upon in 1976 and whether they represent a step forward in Mexico's process of spatial planning.